Wind energy in the Western Cape : examining the role of carbon finance in the development of wind energy projects - White, Rebecca (Department of Environmental and Geographical Science, 2024)
The Western Cape is at an interesting juncture with regards to wind energy. There are several projects at implementation or planning stage - large scale, small scale and microwind projects. There are significant problems within the current electricity supply industry (ESI), which is reliant on coal-fired electricity generation in Mpumalanga and some power plants in the Western Cape. The ESI and electricity distribution industry (EDI) need reforming, and processes have been set in motion to establish six new Regional Electricity Distributors (REDs) - RED One is based in Cape Town. There is also growing energy demand and a continuing government commitment to electrification for all. Wind energy projects could help to meet demand and ease problems of supply. The costs of wind energy project development are falling globally, but they remain high in comparison to conventional fossil-fuel powered generation, such as coal. Furthermore, South Africa has high levels of carbon dioxide (CO2) emissions per capita. CO2 is one greenhouse gas (GHG) which contributes to global climate change. Wind energy projects could be used to mitigate the environmental costs of coal-fired electricity production, by replacing some conventional capacity. South Africa is a signatory to the Kyoto Protocol, which is an international agreement to reduce GHG emissions. Although South Africa, a Non-Annex I country, does not yet have a target to reduce GHG emissions, it can trade its emissions with capped (Annex I) countries. The Clean Development Mechanism (COM) offers an opportunity to gain revenue from carbon emissions reductions (CERs) through such carbon trading. Internationally, wind power projects rank third out of twenty three in terms of the number of projects in the COM pipeline. The Western Cape is a case study that allows the relationship between wind power and the COM to be explored. This research considers whether carbon trading can help the financial viability of wind energy projects. CER revenues are shown to make a positive difference to the financial viability of wind energy projects. The revenues can reduce required bulk electricity tariffs by 7-8c/k:Wh, which brings the cost of wind energy closer to that of coal-fired electricity generation. Recommendations from the research include: • CER revenues could make green electricity more attractive to consumers by reducing the premium paid for electricity from wind energy projects. • If wind can compete with conventional supply during peak hours, through system management of variability, consumers are more likely to consider purchasing green electricity. • Greater public awareness could raise demand for renewable energy, creating a willingness to pay a premium for green electricity. • Experience with wind should reduce the perceived risks of wind energy projects. Hence there should be investment in demonstration projects. • Advice and support for projects at a provincial and local scale is needed. • Small scale wind energy projects can be bundled to ease the CDM process. • Micro-wind should be considered. Payment can be offered for avoided use of grid electricity. • Offshore wind resources and energy potential should be researched further. • The REFSO capital subsidy could be used to help early wind energy projects cover CDM transaction costs. • REFSO could establish a form of FIT that sets a price for renewable energy, enabling REDs and municipalities pay a premium for green electricity and distribute it at an affordable price (or at least a smaller premium) to customers. This would be effective now that there is a national medium term target in place. Given the current supply problems in South Africa, an FIT is likely to be a long term target. • RED One should incorporate renewable energy into its portfolio, setting a target for its share of the energy mix. REDs can negotiate PPAs that allow wind energy projects to be profitable. • There should be continued restructuring of the ESI to give IPPs easier access to the market. • The EIA and other approval processes should be eased through the implementation of wind energy strategies and spatial planning in the Western Cape. • New and accurate wind resource assessments are needed in order to plan for wind in the Western Cape and reduce costs for small scale projects. • The avoided costs of coal must be reflected in the price charged for electricity to allow alternative forms of energy to compete. An economic evaluation of wind would be beneficial. • Wind should be combined with other RETs to create portfolios of renewable energy that provide an effective energy mix specific to the Western Cape's natural energy resources.